The future of finite element technology - the challenge ahead - Sahari, Barkawi; Che Muda, Zakaria (1988)
This paper introduces finite element method as a research tool for engineers and applied scientist. It gives a review of the current software packages available and their capabilities. The paper discusses the development of the next generation of finite element software packages. The challenge to the researcher in selecting and using the package and the relationship between finite element approach and experimental approach to research will also be discussed. The paper also discusses the current state of the finite element program package development being carried out at UPM.